Cronologia e metamorfose da indumentária espartilho - Silva, Fabio Junior da (2014)
The aim of this research is the analysis of the corset dress, addressing the metamorphic transformations occurred throughout history. The research aims to address the aesthetic and symbolic aspects and behavior of society towards the attire. A discussion of the approach corset in menswear, using arguments favorable to arouse the interest of the man in the XXI century. So inserted a brand new corset market and tailoring a model specifies observing the male body.